Answer:
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
Step-by-step explanation:
![9-4(2x-1)=45](https://tex.z-dn.net/?f=9-4%282x-1%29%3D45)
First, we expand the equation using the distributive rule:
![x(y-z)=xy-xz](https://tex.z-dn.net/?f=x%28y-z%29%3Dxy-xz)
Hence, ![9-4*2x-4*-1=45](https://tex.z-dn.net/?f=9-4%2A2x-4%2A-1%3D45)
Simplify: ![9-8x+4=45](https://tex.z-dn.net/?f=9-8x%2B4%3D45)
Add like terms:
![13-8x=45](https://tex.z-dn.net/?f=13-8x%3D45)
Subtract 13 from both sides: ![-8x=32](https://tex.z-dn.net/?f=-8x%3D32)
Divide both sides by -8:
![x=-4](https://tex.z-dn.net/?f=x%3D-4)
Answer:
137
Step-by-step explanation:
because you have to add the nubers
Answer:
of answer Is A choose 1 answer positive negative neiter positive nor negative - the sum Is zero
Step-by-step explanation:
Answer:
(x+7)(x-7)
Step-by-step explanation:
x²-49
=x²-7²
=(x+7)(x-7)
Answer:
Step-by-step explanation:
one circle, lets name it x, Circumference(x)=2*3.14*r= 3.14*d, where d is the diameter
C=2*11*3.14
circle y= Circumference(y)=3.14*2*4
ratio of the radii
C(x)/C(y)=(2*11*3.14)/(2*4*3.14)=11/4= 2 3/4